2013
DOI: 10.1017/s1041610213001592
|View full text |Cite
|
Sign up to set email alerts
|

Depression and other behavioral and psychological symptoms of dementia – separate research worlds in need of a common understanding

Abstract: Depression and other behavioral and psychological symptoms of dementia -separate research worlds in need of a common understandingTerms to describe the behavioral and psychological symptoms commonly seen in dementia, including "Behavioral and Psychological Symptoms of Dementia" (BPSD), "non-cognitive symptoms," and "neuropsychiatric symptoms," were introduced in the 1980s and 1990s to draw attention to the heterogeneous group of symptoms that, distinct from cognitive deficits, are commonly seen in dementia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…In a guest editorial we discussed that the populations used in studies of depression and BPSD are often not quite comparable and that the results therefore cannot be readily extrapolated. 11 Finally, we showed that studies investigating symptom groups show relatively consistent results, although there remains a large amount of individual variability. 10 Studying covariates that may be associated with higher persistence of BPSD, including impairment in activities of daily living, 27,32,64 as well as medication use, 38,46 could improve understanding of potential mechanisms involved in the presence and persistence of BPSD.…”
Section: Future Researchmentioning
confidence: 78%
See 2 more Smart Citations
“…In a guest editorial we discussed that the populations used in studies of depression and BPSD are often not quite comparable and that the results therefore cannot be readily extrapolated. 11 Finally, we showed that studies investigating symptom groups show relatively consistent results, although there remains a large amount of individual variability. 10 Studying covariates that may be associated with higher persistence of BPSD, including impairment in activities of daily living, 27,32,64 as well as medication use, 38,46 could improve understanding of potential mechanisms involved in the presence and persistence of BPSD.…”
Section: Future Researchmentioning
confidence: 78%
“…Studies reporting on minor depression or depressive symptoms only or depression as part of BPSD were included (as discussed in two previous publications). 9,11 From 5923 identified articles 48 were selected for inclusion after the abstract and full-text selection stages. Cross-referencing resulted in an additional 11 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The causal relationship between these conditions remains uncertain, because the prevalence of both increases with advancing age, and there is a paucity of prospective studies. 12 The causal relationship between these conditions remains uncertain, because the prevalence of both increases with advancing age, and there is a paucity of prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between psychological distress and cognitive decline is bidirectional and complex. 12 The causal relationship between these conditions remains uncertain, because the prevalence of both increases with advancing age, and there is a paucity of prospective studies. 13 Some studies have found that depression does not precede cognitive decline, 14,15 whereas others concluded that depression is a risk factor for incident dementia.…”
Section: Discussionmentioning
confidence: 99%